LEKTUR KLASIK PENDIDIKAN ISLAM GENRE PSIKOLOGI - Nadia, Mely; Ginting, Lusinta Rehna (Jurnal Bilqolam Pendidikan Islam, 2021)
The discussion about the soul (al-nafs) in the Islamic world has been started since the emergence of Islamic thinkers on the historical stage. Beginning with the collapse of the Greek-Roman civilization and the movement of translation, commentary and original literature carried out by Islamic thinkers, especially during the Abbasid Daula, the essence of Greek thought was lifted and enriched. The development of psychology if traced through classical Islamic literature, it turns out that there is no separation of scientific disciplines. Psychology is better known as the science of the soul or ulumun nafs. The methodology used in this discussion is the search for references in the form of books and digitization. And the result is one of the Islamic leaders who study psychology, namely Abu Ali al-Khozin Ahmad Ibn Muhammad bin Ya'kub and better known as Ibn Miskawaih. The relationship between the human body and soul Ibn Miskawaih explains that under the soul there is the power of reasoning which is not preceded by sensory recognition. With the power of sensory recognition. The soul is able to distinguish between true or not related to the results of the production of the five senses. The difference is done by distributing sensory objects with one another. Ibn Miskawaih emphasizes the superiority of the human soul over animal souls with the power of thinking which is the source of behavioral considerations, which always leads to goodness.